Violência em escolas com características de risco contrastantes - Pereira, Ana Carina Stelko (2009)
The school context was pointed out as favorable in regards to violence prevention efforts. However, Brazilian studies revealed the existence of violence in the schools, in spite of the absence of valid instruments, and most studies without strict scientific methods. In addiction, these studies did not evaluate different violence risk schools, and few investigated its contributing factors. The present study encompasses two parts. Study 1 had as objectives: (a) to develop and conduct the apparent validity of an instrument to assess school violence, and (b) to develop and perform a pilot test of an instrument aimed at assessing school employees` perception about how a school violence prevention program should be. Study 2 characterized the violence experienced in three schools with diverse risk indicators, according to multiple informants, as well as the perception of the staff about school violence prevention, using the instruments developed in Study 1. Participants involved 706 students, from grades 5-8th, 88 employees of three public schools of Curitiba (Southern Brazil) and six researchers in the area of violence. The instruments were efficient and had good acceptance by the participants. Violence rates in the schools were high regardless of the risk that they were exposed to. Antecedents to aggressive behaviors were examined (i.e. to students victims the most frequent motive for aggressions was violent play). It was also shown that the most common modality of violent behaviors, according to victimized students, was name calling. Consequences to aggressive behaviors by students were also indentified, and the most frequent alternative in this regard was nothing happened . In general, students pointed out that the higher risk school did not differentiate from the intermediate risk school or from the minor risk school, although the minor risk school was more associated with violence than the intermediate risk school. According to staff, the higher risk school was more violent, followed by the intermediate school. The higher risk school was more associated with substance abuse by students, the existence of gangs, drug dealing, and possession of weapons. Staff considered relevant to prevent violence in the schools, but only the higher risk school employees declared it to be more important than other objectives. Psychologists and police officers, followed by parents, were the most frequent sources indentified in terms of involvement with school violence prevention programs. In conclusion, the present study was able to characterize how school violence presents itself, and to investigate contributing variables to the problem. Nevertheless, it is important to replicate the study, and to perform other steps in terms of validation of the instrument, as well as covering the aspects needed for intervention studies, in accordance with the literature.